The Effectiveness of Giving Tomato Juice and Cucumber Juice in Reducing Hypertension In Second and Third Trimester Pregnant Women in PMB Lamria - Desy Novi Yanti; Achmad Fauzi (Universitas Malahayati Lampung, 2023)
ABSTRACT Pregnancy is the process of the meeting of an egg cell and a sperm cell so that fertilization occurs, followed by implantation until the birth of the fetus. Pregnancy normally lasts 280 days or 40 weeks or 9 months.). 40 weeks of pregnancy is called a term pregnancy (term). Hypertension is systolic and diastolic blood pressure 140/90 mmHg. Measurement of blood pressure is done at least 2 times 4 hour intervals. An increase in blood pressure 30 mmHg and an increase in diastolic blood pressure 15 mmHg as hypertension parameters are no longer used. The purpose of this study was to identify changes in blood pressure between administration of tomato juice and cucumber juice to pregnant women in the second and third trimesters. In this study, the researcher used a true experiment design pretest-posttest with control grub. The sample in this study were pregnant women in the second and third trimesters with hypertension as many as 28 people, the sampling technique used was total sampling. Research results Based on the results it is known that 14 respondents who were given cucumber juice mean post test rank of 15.79 while the other 14 respondents who were given tomato juice mean post test rank of 13.21. Based on the Mann Whitney test, the p-value was 0.363. Because the p-value is 0.363 (0.05), it can be concluded that there is no significant difference in the decrease in diastolic blood pressure in the second trimester and third trimester pregnant women with hypertension between those given cucumber juice and tomato juice. Conclusion and Suggestions There is no significant difference in the decrease in systolic and diastolic blood pressure in pregnant women in the second and third trimesters with hypertension between those given cucumber juice and tomato juice. Keywords: Tomato Juice, Cucumber Juice, Pregnancy, Hypertension ABSTRAK Kehamilan adalah proses bertemunya sel telur dan sel sperma sehingga terjadi fertilisasi, dilanjutkan implantasi sampai lahirnya janin. Proses kahamilan normalnya berlangsung selama 280 hari atau 40 minggu atau 9 bulan. Kehamilan 40 minggu disebut kehamilan matur ( cukup bulan ). Hipertensi ialah tekanan darah sistolik dan distolik 140/90 mmHg. Pengukuran tekanan darah sekurang-kurangnya dilakukan 2 kali selang 4 jam. Kenaikan tekanan darah 30 mmHg dan kenaikan tekanan darah distolik 15 mmHg sebagai parameter hipertensi sudah tidak di pakai lagi. Tujuan penelitian ini untuk mengidentifikasi perubahan tekanan darah antara pemberian jus tomat dan jus mentimun pada ibu hamil trimester II dan III. Dalam penelitian ini peneliti menggunakan Desain ( true experiment design pretest-postest with control grub ). Sampel dalam penelitian ini adalah ibu hamil trimester II dan III dengan hipertensi sebanyak 28 orang, tekhnik pengambilan sampel yaitu menggunakan total sampling. Berdasarkan hasil penelitian diketahui bahwa pada 14 responden yang diberikan jus mentimun mean rank post test sebesar 15,79 sedangkan 14 responden lainnya yang diberikan jus tomat mean rank post test sebesar 13,21. Berdasarkan uji Mann Whitney, didapatkan nilai p-value 0,363. Karena nilai p-value 0,363 α (0,05), maka dapat disimpulkan bahwa tidak ada perbedaan yang signifikan penurunan tekanan darah diastol pada ibu hamil trimester II dan trimester III yang hipertensi antara yang diberikan jus mentimun dan jus tomat. Tidak ada perbedaan yang signifikan penurunan tekanan darah sistol dan diastole pada ibu hamil trimester II dan trimester III yang hipertensi antara yang diberikan jus mentimun dan jus tomat. Kata Kunci: Jus Tomat, Jus Timun, Kehamilan, Hipertensi